Human Capital dan Pertumbuhan Ekonomi di Negara Berpenduduk Muslim - Cut Muftia Keumala; Ratna Farida; Neni Triana; Mulia Andirfa (Sekolah Tinggi Ilmu Administrasi Nasional, 2023)
This report aims to empirically investigate the relationship between economic growth based on the theory of Shultz and Kuznets and human capital through health and education in Muslim nations. The results will then be compared between countries. Then, analyze it considering Al-Quran interpretations as a contributor to human capital development. The empirical findings are based on examining a panel data set for Muslim countries from 1990 to 2020. This study interprets Qur'anic verses to explain how Islam characterizes human capital using content analysis methodology. In developing Muslim nations, life expectancy, infant mortality, and population growth are significant determinants of Gross domestic product (GDP) per capita. In contrast, education variables, such as literacy rate and gross enrollment, have a negligible impact on per capita GDP. In contrast to the case with output in developed nations, education level significantly impacts per capita GDP, whereas health variables have no effect.